Analysis of Column Compressive and Adhesive Strengths of Laminated Wood From Pine Pallet Wood Waste and Mahogany as Reinforcement - Arnandha, Yudhi; Indraswari, Mufida; Firmansyah, Dedy (Universitas Negeri Yogyakarta, 2023)
In Indonesia, the increasing demand for wood as an industrial material and the decline in its production rate, which is usually due to illegal logging, causes the emergence of less efficient wood waste. And one of the methods for efficiently utilizing these waste is through lamination. Accordingly, lamination is a technique that involves the gluing of two or more pieces of wood together. Therefore, the purpose of this study was to determine the value of the adhesive and compressive strength of laminated columns between pine pallet waste and mahogany wood reinforcement. The adhesive strength of 20, 30, 40, and 50 MDGL variations joined together using PVAc glue, as well as the compressive strength with variations of T0 (Pine-Pine-Pine-Pine-Pine), T1 (Mahogany-Pine-Mahogany), T2 (Mahogany-Pine-Mahogany-Pine), and T3 (Mahogany-Pine-Mahogany-Pine-Mahogany) were tested in this study. Furthermore, the adhesive and compressive strength tests were in accordance with the ASTM D905-03 standard and the SNI 03-3958-1995, respectively. The adhesive strength test was carried out at the Building Materials Laboratory, Civil Engineering and Planning Study Program, and Faculty of Engineering at the Yogyakarta State University, while the compressive strength test was performed at the Structural Laboratory, Civil Engineering Department, as well as the Engineering Faculty of Tidar University. Data were then analyzed using the one-way ANOVA test and the results of each variation's adhesive strength test were 1.359 MPa, 564 MPa, 1.699 MPa, and 1.558 MPa for the 20, 30, 40, and 50 MDGL MDGL variations respectively. Furthermore, the results of the compressive strength test with variations T0, T1, T2, and T3 were 6.158 MPa, 7.366 MPa, 7.135 MPa, and 6.923 MPa respectively. It was concluded that the highest adhesive strength was at 40 MDGL and the highest compressive strength was at variation T1 (Mahoni-Pinus-Mahoni).